A hora de Macabéa e a problemática do sujeito psicanalítico na literatura e no cinema - Santos, Ray da Silva (2019)
This dissertation consists of a study about the notion of subject, according to the FreudoLacanian perspective, considering the character Macabéa, from the book A Hora da Estrela and its homonym adaptation. The research is based on the following questions: how can the subject be explored through the character Macabéa, both in the literary and in the cinematographic narrative, based on the presuppositions of psychoanalysis? That is, in what way are these narratives structured in order to represent a subject, taking into account how this notion is constituted by Freud and Lacan? To do so, we outline the following steps as specific objectives: a) collaborate in interdisciplinary studies between literature, cinema and psychoanalysis; b) show traces of affinities and distances between literature, cinema and psychoanalysis; c) to investigate and to understand the notion of psychoanalytic subject from the character Macabéa, being based on the categories of analysis coming from the theoretical-methodological reference. We emphasize that, as a research methodology, we have the theoretical discussions of Freud and Lacan followed by the qualitative analysis of the book and film, which we consider as texts, consequently, holders of statements that, like the analysand's dreams and speech, reveal something more from the enunciator. Having said this, it is noticed that literature and cinema represents the man and his relation with the environment, desires and their phantoms, through language; in these fields of representation, we see narrators and characters living experiences, resolving internal and external conflicts, providing us with a fertile space for the discussion about subjectivity. It is noteworthy that the rational, indivisible, Cartesian subject, over time and with the theoretical and clinical advances of psychoanalysis, has revealed a divided form, a binarism formed by one rational part and the other unknown to itself. Such conceptions of the problematic of the psychoanalytic subject directly interfere with the way in which we conceive the literary and cinematographic work, because we know that the characters and the narrator during the development of the narrative can say something more about the subject of the unconscious. We realized that in the spaces between signifiers, the existence of voids that, in turn, reveal effects of the unconscious in the character, resulting in enunciations composed of enigmas and traces of desire, making, through the psychoanalytic look, signifier, the question of subject, everything referring to the sign "Macabéa".